Application-Based Assembled Edu Media to Stimulate Early Childhood Alphabet Recognition Abilities - Sari, Luh Julia; Handayani, Dewa Ayu Puteri (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Currently, the only learning media available are books and letter posters which are used to learn to recognize letters, so that in developing aspects of language development, one of them is that children's language literacy is less than optimal. Research and development of assemblr edu media in stimulating alphabet recognition ability for early childhood children. The purpose of this study was to determine whether the design and development of the educational media assembly was appropriate for stimulating the ability to recognize letters in kindergarten. This study stimulate the ability to recognize letters in early childhood children with attractive digital media. The model used was ADDIE. The instrument used to collect data was a questionnaire. The validity test of this assessment instrument was carried out through content validity testing (expert/expert test). The developed instrument will be tested by two media experts, two material experts, and ten student responses. Based on the validity test by two experts, the instrument validity value = 1 was obtained, which stated that the validity of this media instrument has a very high criterion and is worthy of use. Whereas Based on the results of the media expert validity analysis, a score of 93.18% was obtained, the material expert validity result obtained a score of 100 and the child response trial obtained a score of 97.5%. So that this research is "Valid" with a very good qualification and is worthy of stimulating the ability to recognize letters in early childhood children.